2021
DOI: 10.3390/biomedicines9121788
|View full text |Cite
|
Sign up to set email alerts
|

A Polyclonal Antibody Raised against the Burkholderia cenocepacia OmpA-like Protein BCAL2645 Impairs the Bacterium Adhesion and Invasion of Human Epithelial Cells In Vitro

Abstract: Respiratory infections by bacteria of the Burkholderia cepacia complex (Bcc) remain a life threat to cystic fibrosis (CF) patients, due to the faster lung function decline and the absence of effective eradication strategies. Immunotherapies are regarded as an attractive alternative to control and reduce the damages caused by these infections. In this work, we report the cloning and functional characterization of the OmpA-like BCAL2645 protein, previously identified and found to be immunoreactive against sera f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…P. aeruginosa F69A isolate IST27 [ 22 ], B. cenocepacia K56-2 [ 23 ] and B. multivorans BM1 [ 24 ] were used in this work and maintained in PIA (Pseudomonas Isolation Agar plates; Becton Dickinson, Heidelberg, Germany). When in use, Escherichia coli was maintained in LB plates [ 21 ]. When necessary, media were supplemented with 150 μg/mL ampicillin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. aeruginosa F69A isolate IST27 [ 22 ], B. cenocepacia K56-2 [ 23 ] and B. multivorans BM1 [ 24 ] were used in this work and maintained in PIA (Pseudomonas Isolation Agar plates; Becton Dickinson, Heidelberg, Germany). When in use, Escherichia coli was maintained in LB plates [ 21 ]. When necessary, media were supplemented with 150 μg/mL ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…The CFBE41o-human bronchial epithelial cell line [ 25 ], was used in this study. Cells were cultured under humidified atmosphere at 37 °C with 5% CO 2 , as previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B. cenocepacia homolog, BCAL2645, is another one of the lipoproteins identified via Sousa et al’s surface trypsin shaving study, providing evidence that it is a potential surface-exposed target for antibody binding [ 190 ]. Further, Seixas et al recently demonstrated that polyclonal antibodies towards BCAL2645 impair adhesion and invasion of CFBE41o- cells by B. cenocepacia [ 203 ]. The ability of these antibodies to impede adherence suggests a possible mechanism of protection if this antigen were to be used in vaccination.…”
Section: General Outer Membrane Proteins: Lipoproteinsmentioning
confidence: 99%
“…The use for treatment of other bacterial infections has been less common. Our group recently showed that a pAbs against an OmpA-like protein from Burkholderia cenocepacia greatly impairs the ability of these bacteria to adhere and invade human epithelial cells in vitro [41]. Both the adhesion and invasion are highly important steps in the infection process.…”
Section: Conventional Mammalian Polyclonal Antibodiesmentioning
confidence: 99%